2016
DOI: 10.1142/s0219877016400010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organizational Learning, Transformational Leadership, and Market Orientation on Firm Performance

Abstract: The purpose of this study is to examine the effects of organizational learning, market orientation, and transformational leadership on the organizational innovation and firm’s performance amongst the firms performing in Turkey. Using LISREL, structural equation-model, the data gathered from 330 employees were used to identify the variables that significantly affect the firm’s performance. The results indicated that 32% of firm’s performance is explained by the organizational innovation and market orientation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…This study supports the research which states that knowledge sharing positively affects the organizational innovativeness [16]; [4]; [5]. Other results showed that leadership types had significant impact on the organizational innovation, which is different from previous research [10]; [25]. There is indirect relationship between transformational leadership and organizational performance, mediated by organizational innovativeness.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This study supports the research which states that knowledge sharing positively affects the organizational innovativeness [16]; [4]; [5]. Other results showed that leadership types had significant impact on the organizational innovation, which is different from previous research [10]; [25]. There is indirect relationship between transformational leadership and organizational performance, mediated by organizational innovativeness.…”
Section: Discussionsupporting
confidence: 77%
“…Study have found significant direct and indirect association between leadership and knowledge sharing [5], while other study found no relationship between transformational leadership and knowledge sharing besides transactional leadership [9]. Transformational leadership is also found to have insignificant impact on the organizational innovation and suggests future research on the relation of knowledge sharing as important antecedent of organizational innovation [10]. Latest studies show significant relationship between leadership styles and organizational performance [11]; [6], while other study show insignificant relationship between transformational leadership and organizational performance, but mediated indirectly by job satisfaction [12].…”
Section: Literature Reviewmentioning
confidence: 79%
“…Leaders share a vision with followers and provide direction, energy, and support for organizational achievement (García‐Morales, Bolívar‐Ramos, & Martín‐Rojas, ). Leaders stimulate their followers to unlearn old methods and relearn new ways of solving problems, creativity (Bai, Lin, & Li, ), organizational learning, market orientation, organizational innovation, and firm performance (Calisir et al, ). Leaders are powerful wellsprings of organizational rents and consequently enhanced performance through sustainable competitive advantage (García‐Morales et al, , ) and managerial performance (Nguyen et al, ).…”
Section: Model and Research Hypothesesmentioning
confidence: 99%
“…Numerous studies have analyzed the direct influence of transformational leadership on organizational performance(García-Morales et al, 2008;Nguyen, Mia, Winata, & Chong, 2017;Saeidi et al, 2015), while others have analyzed this relationship through intervening variables such as organizational knowledge and innovation(Calisir, Gumussoy, Basak, & Gurel, 2016;García-Morales et al, 2008), human capital-enhancing human resource management(Zhu, Newman, Miao, & Hooke, 2013), and absorptive capacity(García-Morales et al, 2008).…”
mentioning
confidence: 99%
“…Its government largely promotes a policy of economic liberalisation by lowering trade and non-trade barriers, and by facilitating labour mobility. Although previous research has established the performance benefits of MO for organisations competing in Turkey (Calisir et al, 2016), MO is not a ubiquitous strategic orientation in Turkey (Köseoglu et al, 2015). Amid its economic development, Turkey has been involved in continuing geopolitical struggles; seen recent political upheavals; exhibited ambiguous business conditions and a high level of power asymmetry among organisations and important stakeholders; and faced numerous economic challenges stemming from short-term fluctuations, foreign influence, and a recent coup attempt (Culpan and Gursoy, 2009;Polataglu, 2007).…”
Section: Introductionmentioning
confidence: 99%